ANALISIS VALIDITAS BUKU AJAR UNTUK SISTEM PERKULIAHAN E-LEARNING PADA MATA KULIAH KIMIA DASAR DI FKIP UMMY SOLOK - -, Afrahamiryano -; Ariani, Dewi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
E-learning lecture system is a lecture system that has been the talk of the world for several years. With regard to this e-learning process, there will still be teaching materials that are made. Teaching materials in the form of material for one semester published through e-learning media. Each teaching material needs to go through the validation process. So far, teaching materials created by lecturers only to support the lecture process, not many lecturers who validate the teaching materials given to students. The importance of validation of teaching materials is necessary to see the suitability of teaching materials to business / industry needs, so that the teaching materials are appropriate and suitable for use in learning. Therefore, the research is conducted to determine the validity of this resource. The formulation of the problem in this research is how the validity of basic chemistry textbook content for e-learning lecture system in FKIP UMMY Solok? To answer the problem formulation used R & D research method using 4D development model. The content validation of Textbook is done by expert consideration method and for data analysis of expert consideration result, used CVR index developed by Lawshe. Validation of this textbook aims to see the suitability of the content or substance of teaching materials. Triangulation results of expert consideration data obtained information that the validity of Basic Chemistry Basic textbook relevant / viable in terms of content and can be used for e-learning lecture system.